Investigation of Turkey's PISA 2015 Science Achievement and Associated Variables Using Hierarchical Linear Modeling - YILDIZ, Mustafa; ERDAŞ KARTAL, Eda; MESCİ, Günkut (Necatibey Faculty of Education Electronics Journal of Science and Mathematics Education, 2020)
The purpose of this study is to investigate the variables related to science achievement of high school students in Turkey portion of PISA 2015, by using hierarchical linear modeling (HLM) approach. The findings revealed that the relationship between the science achievement and demographic characteristics of the students is stronger than the relationship between science achievement and the affective domain as well as the learning environment. Based on these findings, it is thought that improving students’ science achievement is possible by taking into account the variables that affect the success, especially with improvements that can provide equal opportunities in the context of demographic variables and the construction of inclusive school systems.
Keywords: 5. Gender equality; 4. Education; 10. No inequality